Imagined globalization - García Canclini, Néstor, 1939- (Latin America in translation/en traducción/em tradução, 2014)
A leading figure in cultural studies worldwide, Néstor García Canclini is a Latin American thinker who has consistently sought to understand the impact of globalization on the relations between Latin America, Europe, and the United States, and among Latin American countries. In this book the author considers how globalization is imagined by artists, academics, migrants, and entrepreneurs, all of whom traverse boundaries and, at times, engage in conflicted or negotiated multicultural interactions. The author contrasts the imaginaries of previous migrants to the Americas with those who live in transnational circuits today. He integrates metaphor and narrative, working through philosophical, anthropological, and socioeconomically grounded interpretations of art, literature, crafts, media, and other forms of expression toward his conclusion that globalization is, in important ways, a collection of heterogeneous narratives. This book advocates global imaginaries that generate new strategies for dealing with contingency and produce new forms of citizenship oriented toward multiple social configurations rather than homogenization. This text includes a significant new introduction by George Yúdice and an interview in which the cultural theorist Toby Miller and García Canclini touch on events including the Arab Spring and Occupy Wall Street.